APPLYING OF NUMBERED HEAD TOGETHER LEARNING MODEL ON EIGHT THEMES MY PLACE AREA TO IMPROVE SOCIAL ATTITUDE OF FOURTH GRADE STUDENT IN STATE- PRIMARY SCHOOL 1 TEGALGONDO KLATEN AT 2017/2108 ACADEMIC YEAR - Damantari, Hening; Chumdari, Chumdari; Wahyuningsih, Siti (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
The purpose of this research was to improve social attitude in tematik learning using Cooperative Learning Model type Numbered Head Together (NHT)  in fourth grade students of State-Primary School I Tegalondo Klaten at 2017/2018. The form of this research was a classroom action research that consist three cycles and each cycle consisting of two meetings.The data collection techniques was used observation, interview, and documentation. The data validity were triangulation of resources and technique. The data analysis technique was used interactive model. The result showed that the Numbered Head Together Learning Model can improve social attitude in fourth grade students of State-Primary School I Tegalondo Klaten at 2017/2018. This can be seen in the amount of students who achieve social attitudes have been cultured categories. From 34 students on pre-cycle as many as 15 students or 44.12% with an average of 3.18. Increased  in first cycle  were 17 students or 50% with an average of 3.32. In second cycle were 24 students or 70.59% with an average of  3.45. In the third cycle of 33 students or 97.06% with an average of 3.62. The conclusion of this research was application of  Numbered Head Together (NHT)  Learning Model can  improve  social attitude  in the fourth grade students of State-Primary School I Tegalgondo Klaten at 2017/2018.